Revealed wisdom : studies in Apocalyptic in honour of Christopher Rowland - Rowland, Christopher, 1947-; Ashton, John F. (Ancient Judaism and Early Christianity, 2014)
A collection of twenty-one essays clustered around the theme of apocalyptic-revelations of hitherto undisclosed divine mysteries to human seers, either directly or through the mediation of an interpreting angel. Preliminary essays on the Book of Job, Messianism, and apocalyptic ethics are followed by five studies centred upon Jewish apocalypses composed around the turn of the era, two anonymous, three pseudonymous, and four essays on New Testament writers, two on Paul, one on Mark, and one on John. A reflection upon an early Islamic convert from Judaism, emphasizing the 'Abrahamic-lexicon' common to all three religions of the book, is succeeded by essays on two medieval Christian visionaries, Joachim of Fiore and Francis of Assisi. After a further essay on a little known Syriac apocalyptic text the volume concludes with studies of four different aspects of the Book of Revelation itself.